ANALISIS IMPLEMENTASI PUBLIC SAFETY CENTER 119 DI KABUPATEN WONOGIRI - Naufal Bahri Maulana; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Health problems are one of the things that cannot be avoided from the life of the people of Wonogiri Regency. The geographical area that is outskirt of the provincial center and the low population makes Wonogiri's health quality score still low. Infant mortality rate, under-five mortality rate, and maternal mortality rate in Wonogiri Regency is ranked 20th out of 35 regencies/cities in Central Java Province. Efforts to improve the health quality of the Wonogiri people continue to be carried out by the Wonogiri Regency Government through the Panca Program of the Wonogiri Regent, one of which includes 'Sehat Rakyate' to pass Regent Regulation Number 9 of 2021 concerning the Formation of a Public Safety Center 119. The formation of this regulation is expected to be able to realize an Emergency Response System Integrated in Wonogiri Regency and increasing the number of Wonogiri public health quality. This study aims to analyze the process of implementing Public Safety Center 119 and analyze the driving and inhibiting factors in its implementation in Wonogiri Regency. The research method used in this research is descriptive qualitative using primary data sources obtained through in-depth interviews and field observations as well as secondary data. . In this study it was found that the formation of the Public Safety Center 119 was appropriate with the problems faced by the Government of Wonogiri Regency. The implementation of the Public Safety Center 119 has also been going well although there are still problems regarding the implementation system. Positive acceptance from the people of Wonogiri towards the formation of the Public Safety Center 119 policy. In the implementation of this program there are also driving factors, namely facilities and convenience, as well as inhibiting factors, namely service procedures and scope